Faktor Strategis Motivasi Belajar Dan Dampaknya Pada Hasil Belajar Matematika Di MTs - Darsinah, Darsinah (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2020)
This study aims to: 1) Test the role of the learning environment and learning resources together, towards mathematics learning outcomes, indirectly through learning motivation. 2) Testing the role of the learning environment and learning resources simultaneously has a direct effect on learning motivation. 3) Test the role of learning motivation on mathematics learning outcomes. The study population of 246 students, a sample of 153 students. Research uses a quantitative correlational approach. Data collection uses questionnaires and documents. Data analysis techniques used path analysis, classical assumption test, model accuracy test, and estimator parameter accuracy test. Structural equation for the relationship between variables as follows: Z = 0.196 X1 + 0.171 X2 + 0.193 Y + 0.911, meaning that if the learning environment, learning resources, and learning motivation variables rise one level then successively have an effect each by 0.196; 0,171; 0.193 against mathematics learning outcomes. The results of the study: 1) There is a simultaneous role of the learning environment and learning resources, towards mathematics learning outcomes, indirectly through motivation to learn mathematics. 2) There is the role of the learning environment and learning resources simultaneously have a direct effect on learning motivation. 3) There is a role for learning motivation towards mathematics learning outcomes.